2013
DOI: 10.1021/jf4002507
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Tiger’s Milk Mushroom, Lignosus rhinocerotis (Cooke) Ryvarden, from Different Developmental Stages

Abstract: The chemical composition of the tiger's milk mushroom (Lignosus rhinocerotis) from different developmental stages, i.e., the fruit body, sclerotium, and mycelium, was investigated for the first time. The fruit body and sclerotium of L. rhinocerotis were rich in carbohydrates and dietary fibers but low in fat. Protein levels in L. rhinocerotis were moderate, and all essential amino acids, except tryptophan, were present. The mycelium contained high levels of potassium, phosphorus, magnesium, riboflavin, and nia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 21 publications
5
29
1
Order By: Relevance
“…These essential unsaturated fatty acids cannot be synthesised in mammalian tissue, therefore, must be obtained from the diet [23]. The identified major compound, linoleic acid, was not obtained in the findings of Lau et al [24]. However, in this study, only linoleic acid demonstrated antiinflammatory activity via reduction of nitric oxide production without exerting any cytotoxic effect on the cells.…”
Section: Lipids From Lignosus Rhinocerotiscontrasting
confidence: 48%
“…These essential unsaturated fatty acids cannot be synthesised in mammalian tissue, therefore, must be obtained from the diet [23]. The identified major compound, linoleic acid, was not obtained in the findings of Lau et al [24]. However, in this study, only linoleic acid demonstrated antiinflammatory activity via reduction of nitric oxide production without exerting any cytotoxic effect on the cells.…”
Section: Lipids From Lignosus Rhinocerotiscontrasting
confidence: 48%
“…It is also popularly referred to as the “tiger’s milk mushroom” (“ cendawan susu rimau ” in Malay) by the local and indigenous communities in Malaysia. Previous chemical investigations on L. rhinocerotis focused mainly on its proximate composition [1] and other nutritional attributes, such as fatty acids, vitamins, minerals, and β-glucans [2] ; in particular, the physicochemical and functional properties of the sclerotial dietary fibres have been extensively investigated [3] . Among the bioactive components in L. rhinocerotis , the water-soluble, polysaccharide-protein complexes and β-glucans have been thoroughly studied for anti-tumour [4] and immunomodulatory effects [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites isolated from extracts of other mushrooms have been reported to potentiate NGF-induced neurite outgrowth in PC-12 cells, including cyathane diterpenoids isolated from methanolic extract of Sarcodon scabrosus and hericenones isolated from ethanolic extract of Hericium erinaceus [38,39]. Sclerotium of L. rhinocerus was reported to have high carbohydrate content including polysaccharides such asglucans, which are bioactive components with anticancer and immunomodulatory activities [40]. Furthermore, chromatographic analysis of L. rhinocerus aqueous sclerotial extracts and genome sequencing of L. rhinocerus sclerotium (cultivar TM02) demonstrated many bioactive secondary metabolites, such as triterpenes, terpenoids, phenolic, and alkaloids [9,41].…”
Section: Rhinocerus Ha and Me Extracts Promoted Neuritementioning
confidence: 99%